Correction to "Interfacial Tension of (Brines + CO2): (0.864 NaCl + 0.136 KCl) at Temperatures between (298 and 448) K, Pressures between (2 and 50) MPa, and Total Molalities of (1 to 5) mol.kg(-1)" - Chow,YTF; Maitland,GC; Stevar,MSP; Trusler,JPM (Journal of Chemical and Engineering Data, 2018)
Li et al.(1) reported interfacial tension measurements between carbon dioxide and the mixed brine (0.864 NaCl + 0.136 KCl) over wide ranges of temperature, pressure and total salt molality. We have determined that their data on the isotherm at 298.15 K for the salt molaity of 0.98 mol·kg–1 are erroneous; results at other temperatures and salt molalities reported in(1) are not affected by the error. We report herein new data, measured at T = 298.15 K and at pressures between (2 and 51) MPa, to replace the corresponding isotherm reported in Table 2 of the original reference.